Pelatihan QRIS dan Inovasi Layanan Antar sebagai Upaya Penguatan Kompetitivitas Toko Kelontong - Tegar Aji Aimar; Alan Maulana Fatony; Aris Puji Purwatiningsih; Amalia Nur Chasanah; Masitha Fahmi Wardhani (Universitas Merdeka Surabaya, 2026)
Traditional grocery stores play an important role in fulfilling the daily needs of rural communities; however, they currently face significant challenges due to changes in consumer behavior and the increasing penetration of modern retail. This Community Service Program (PKM) aimed to enhance the competitiveness of traditional grocery stores through training on the use of the QRIS digital payment system and the development of an innovative WhatsApp-based delivery service. The training was conducted using socialization, demonstration, and direct mentoring methods involving store owners and employees. The results showed an improvement in the digital literacy of store owners, as evidenced by their ability to independently and efficiently operate cashless payment systems. In addition, the implementation of a simple WhatsApp-based delivery service increased customer convenience, expanded service reach, and strengthened customer loyalty. These findings indicate that the integration of transaction digitalization and service innovation can serve as a practical and effective strategy to reinforce the competitive position of traditional grocery stores amid modern market dynamics. This program provides a tangible contribution to empowering traditional retail MSMEs and can be replicated in other grocery stores in residential and rural areas.